2019
DOI: 10.1080/00365521.2019.1660402
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fecal calprotectin and serum C-reactive protein in early prediction of outcome to infliximab induction therapy

Abstract: Background: Fecal calprotectin (FC) and serum C-reactive protein (CRP) are biomarkers of disease activity in Crohn's disease (CD) and ulcerative colitis (UC). We assessed FC, CRP, Harvey-Bradshaw index (HBi), partial Mayo Clinic Scoring (pMCS) and a cytokine panel during infliximab induction to predict therapy outcome. Methods: FC, CRP and clinical indices were evaluated in 123 (76 CD, 47 UC) patients before infliximab induction and after 12 weeks. Responders were monitored 48 weeks for an 'incident' (dosage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…Summarizing these findings, we speculated that IL-6 and TNF-α may be the potential targets related to the therapeutic effects of IFX in CD, though the mechanism was not fully understood. Consistent with our study, Engstrom et al noticed that IL-6 and TNF-α levels were lower in IBD patients after 12 weeks IFX administration (39). Kato et al noted that IL-6 and TNF-α levels were reduced in CD patients after the initial IFX infusion (2 weeks), but not in 14 weeks (40).…”
Section: Discussionsupporting
confidence: 91%
“…Summarizing these findings, we speculated that IL-6 and TNF-α may be the potential targets related to the therapeutic effects of IFX in CD, though the mechanism was not fully understood. Consistent with our study, Engstrom et al noticed that IL-6 and TNF-α levels were lower in IBD patients after 12 weeks IFX administration (39). Kato et al noted that IL-6 and TNF-α levels were reduced in CD patients after the initial IFX infusion (2 weeks), but not in 14 weeks (40).…”
Section: Discussionsupporting
confidence: 91%
“…(a) IL‐17A plays a vital role in the development of inflammation in axSpA patients; meanwhile, a high baseline IL‐17A level indicates a more serious inflammatory condition, which intensifies the efficacy of the TNF inhibitors, thereby causing a higher ASAS40 response rate 20,25 . (b) CRP is a well‐known acute phase inflammatory marker, extensive studies disclose that its high baseline expression is related to an excellent response to TNF inhibitors in autoimmune diseases including RA and Crohn disease and axSpA 21,26,27 . In axSpA patients, we suppose that a high baseline CRP level is correlated with aggravating disease status, including high disease activity and exacerbating inflammatory conditions; in addition, patients with disturbing disease status may benefit more from the TNF inhibitor treatment, thereby, leading to a higher ASAS40 response rate.…”
Section: Discussionmentioning
confidence: 99%
“…20,25 (b) CRP is a well-known acute phase inflammatory marker, extensive studies disclose that its high baseline expression is related to an excellent response to TNF inhibitors in autoimmune diseases including RA and Crohn disease and axSpA. 21,26,27 In axSpA patients, we suppose that a high baseline CRP level is correlated with aggravating disease status, including high disease activity and exacerbating inflammatory conditions; in addition, patients with disturbing disease status may benefit more from the TNF inhibitor treatment, thereby, leading to a higher ASAS40 response rate. (c) Patients with axSpA with a history of TNF inhibitor use may have a higher level of anti-drug antibody compared with the TNF inhibitor naive patients, which would decrease the blood concentration of adalimumab, thereby causing a worse efficacy in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple biomarkers such as serum calprotectin, albumin, and C-reactive protein (CRP) have been studied to estimate the disease severity in CD ( 7 ). Many studies have recently shown that fecal calprotectin (FC) can be used as a non-invasive biomarker of disease activity ( 8 10 ). However, FC might not be increased in patients with CD who predominantly have ileal involvement ( 11 ).…”
Section: Introductionmentioning
confidence: 99%